Criminalistic (forensic) equipment in professional activity of attorney: notion and value - Бишевець, О. В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
On the basis of analyses of criminalistics literature and current legislation, the author has offered its own point of view on role and value of criminalistics (forensic) equipment in advocacy. In the article the author defines following features of technical and forensic equipment using by attorneys in theirs’s professional activity: it has alternative character. In positions of current legislation of Ukraine there is no norm that would fasten the duty of advocate independently to apply facilities of criminalistics technique in criminal realizations. At the same time the article № 42 in the Code of criminal procedure of Ukraine avouches for advocates a right to apply with inhibition of requirements of law technical equipment during realization of judicial actions in that he participates. Thus, an advocate on the discretion decides a question about a necessity to use techno-criminalistics facilities in his professional activity; it’s mediate. Since the procedural function of the advocate to defend a person from suspicion or the charges, he doesn’t make any investigative actions, but only participate in order to ensure the rights and legitimate interests of the person it protects. If the advocate was not involved in participation in investigative (search) actions, he retrospectively studying the materials of criminal proceedings, in particular the protocols of inspection of the scene or individual objects, protocols of interrogations of witnesses, conclusions of forensic examinations. Given the above, the task of the lawyer consists in observing the proper means of forensic techniques used by investigators and forensic experts for detection, fixing and withdrawal of traces of crime; it’s limited by capacity. Because of using the application of technical and forensic equipment by advocates as a guarantee of compliance by investigators and prosecutors of the rights and legitimate interests of the suspect, victim or witness during proceedings, in most cases, defense attorneys need to use audio-video equipment to be able to photograph the venue of the investigation or examination of individual objects that were discovered during carrying out a search, to inspect the documents in sidelong falling light in the ultraviolet or the infrared. As for the manufacturing (using plaster, wax, polymeric materials) copies of footprints, vehicles, tools, hacking and tools, this is done by professionals who have practical skills of identification, fixation and confiscation the traces of crime.

На основі аналізу криміналістичної літератури і положень чинного законодавства України автором запропоновано власне бачення ролі криміналістичної техніки у адвокатській діяльності. Окрему увагу у статті приділено висвітленню сучасних наукових підходів стосовно завдань використання адвокатами техніко-криміналістичних засобів у кримінальних провадженнях та охарактеризовано особливості такого застосування.
КРИМІНАЛІСТИЧНА ТЕХНІКА У ПРОФЕСІЙНІЙ ДІЯЛЬНОСТІ АДВОКАТА: ЗАВДАННЯ ТА ЗНАЧЕННЯ
Keywords: criminalistics; criminalistics knowledge; criminalistic (forensic) equipment; advocacy.; кримінальне провадження; криміналістика; криміналістична техніка; криміналістичні знання; адвокатська діяльність; техніко-криміналістичні засоби.